Roles of ECH system in DTT plasma operations - G. Granucci; F. Auriemma; L. Aucone; B. Baiocchi; N. Bonanomi; F. Braghin; A. Bruschi; D. Busi; I. Casiraghi; L.E. di Grazia; F. Fanale; L. Figini; et al. (Nuclear Fusion, 2024)
The Divertor Tokamak Test (DTT) facility is equipped with auxiliary heating systems in order to be able to load the divertor with a power flux relevant to study the power exhaust issue in a reactor relevant range of parameter. The powerful system is the Electron Cyclotron Heating (ECH) with an installed power of 32 MW in its largest extension. Together with the bulk heating of the DTT plasma, the ECH system will cover several tasks for the plasma operation. This paper summarizes the main characteristics and design choices of the DTT ECH system and the related physics studies, based on the reference DTT plasma, to develop and control the plasma, fulfilling the functional tasks, with the support of simulation activities. Dedicated studies have been carried out to investigate the capability of EC power to assist plasma start-up, stabilize MHD activity and support current ramp up/down. In addition, it has been studied how changes of the ECH power distribution can have an impact on the plasma profiles, affecting the fueling pellet effectiveness and MHD modes.